Implementasi Pembiayaan KUR dengan Akad Murabahah Bil Wakalah Pada Bank Syariah Indonesia Karawaci Tangerang: Tinjauan Fatwa DSN-MUI NO.04/DSN-MUI/IV/2000 tentang Murabahah - Abdul Rachman; Widi Astuti (STES Islamic Village, 2023)
This research undertakes an in-depth investigation into the implementation of People's Business Credit (KUR) financing and the suitability of the Murabahah bil Wakalah contract applied to KUR financing products at Bank BSI KCP Tangerang Karawaci Mutiara. The study aims to assess the adherence to the principles laid out in DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000 on Murabahah. Employing a qualitative descriptive methodology, with a field research approach and juridical-normative analysis, the research scrutinizes the relevant fatwa and regulatory provisions related to the examined matter. Data collection is facilitated through interviews, observations, and documentation of pertinent literature, including books, journals, and official documents pertaining to the research subject. The findings reveal that during the execution of the Murabahah bil Wakalah contract in KUR financing, the goods involved were not yet under the ownership of Bank BSI KCP Tangerang Karawaci Mutiara. Instead, the customers, acting as agents for the bank, completed the purchase of the goods only after simultaneous signing of both the Murabahah and Wakalah contracts. Consequently, the goods were not under the bank's ownership at the time of contract execution. Moreover, the research demonstrates overall compliance with DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000 on Murabahah in the application of the Murabahah bil Wakalah contract in KUR financing products. Nevertheless, certain inconsistencies were identified in the execution of the first provision, specifically point nine, wherein the Murabahah and Wakalah contracts were conducted jointly before the customers made their purchases as agents for the bank. This practice was justified to optimize time efficiency and enhance convenience for the customers. This research suggests to the successful implementation of KUR financing utilizing the Murabahah bil Wakalah contract at Bank BSI KCP Tangerang Karawaci Mutiara necessitates more robust control measures regarding the ownership status of goods at the time of contract execution